Answer:
![y=(1)/(12)(x+2)^(2)+1](https://img.qammunity.org/2023/formulas/mathematics/high-school/1cghzbpgd0nxfkquh40wwg5o0ubi1q0tgq.png)
Explanation:
Given a parabola with the following properties:
• Vertex: (-2, 1)
,
• Focus: (-2, 4)
We want to write an equation for the parabola.
The standard equation of an up-facing parabola with a vertex at (h,k) and a focal length |p| is given as:
![\begin{equation}(x-h)^(2)=4 p(y-k)\end{equation}](https://img.qammunity.org/2023/formulas/mathematics/high-school/xps7ykkflcromchbm4pco4w15l0mb1rn3i.png)
![\begin{gathered} Vertex,(h,k)=(-2,1)\implies h=-2,k=1 \\ Focus,(h,k+p)=(-2,4)\implies h=-2,k+p=4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/igo57fyy4r44i8ecbiyvx4g93dos24t7fz.png)
We solve for p:
![\begin{gathered} k+p=4 \\ 1+p=4 \\ p=4-1 \\ p=3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/y90ztpbnjtyx9bos5aclujnojsevz6k6ks.png)
Substitute the values h=-2, k=1, and p=3 into the standard form given earlier:
![\begin{gathered} (x-(-2))^2=4(3)(y-1) \\ (x+2)^2=12(y-1) \\ \text{ Divide both sides by 12} \\ (1)/(12)(x+2)^2=y-1 \\ \text{ Add 1 to both sides of the equation} \\ y=(1)/(12)(x+2)^2+1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/bym0kckm5fkpdkvhoc78i002ui9zktrmbj.png)
The equation for the parabola is:
![y=(1)/(12)(x+2)^(2)+1](https://img.qammunity.org/2023/formulas/mathematics/high-school/1cghzbpgd0nxfkquh40wwg5o0ubi1q0tgq.png)
The last option is correct.